Ocorrência de Meloidogyne graminis em grama no estado de São Paulo - Oliveira, Samara Azevedo [UNESP] (2015)
Currently, the grasses growing in Brazil is expanding. The biggest consumer market for lawns is the industry of sports, especially football and golf courses. The quality of the lawn in these sports areas is crucial, especially when it comes to golf courses, where any imperfection can prejudice the outcome of the game. The nematode parasites of plants of the genus Meloidogyne, also known the root-knot nematodes, are considered the most economically important because of the intensity of the damage they cause to crops. The main species associated with grasses on golf courses are M. graminicola, M. graminis, M. marylandi, M. naasi, M. minor and M.sasseri. In Brazil Meloidogyne sp. has been reported in esmerald grass roots (Zoysia japonica) in the State of Paraná. The species M. graminicola was detected in rice roots in Rio Grande do Sul and Santa Catarina. In 2006 the species M. graminis, was first detected in South America parasitizing grass roots Tifdwarf shorts on golf course in Venezuela. So far this species has not been reported in Brazil. The objective of this project is to identify the root-knot nematodes found parasitizing roots of grasses of golf courses in the state of Sao Paulo. For this were carried out detailed studies of integrative taxonomy, including morphological and morphometric studies, biology, biochemical, molecular and phylogenetic. All analyzes have confirmed that the species in golf courses in São Paulo state is M. graminis, that characterized the first report of the species in Brazil.